Accumulation of Calcium Crystal in Rat (Rattus norvegicus) Kidney - A'liyatur Rosidah; Sri Widyarti; Sri Rahayu (Journal of Tropical Life Science, 2013)
The aim of this research is to know the effect of tuber Porang flour (Amorphophallus muelleri) to the accumulation of calcium crystal. This research uses 2,5 months old male rats that are orally given by tuber Porang flour from three different location (Klangon, Sumber Baru, and Sumber Bendo) with doses 6 mg/100 gr BW/day for 3 months. Kidneys taken to analyzed distribution of crystal calcium accumulation. Observation of distribution crystal calsium accumulation with microscope of Olympus CX 31 at 400x magnification. The data to be analysed by using test of ANOVA with SPSS 16 for windows. The result of research known that the treatment of tuber Porang flour induce calcium crystal accumulation in rat kidneys. Using tuber porang flour from different location can generate different impact at accumulation of crystal calcium. The lowest calcium crystal accumulation in kidneys with giving Klangon Porang flour that is equal to 8,19±2,17 spot/ area. Consumption of the tuber Porang flour cause the accumulation of crystal calcium in rat kidney.